2020
DOI: 10.1101/2020.12.27.424477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The autophagy activator Spermidine ameliorates Alzheimer’s disease pathology and neuroinflammation in mice

Abstract: Deposition of amyloid beta (Aβ) and phosphorylated Tau along with microglia- and astrocyte-mediated neuroinflammation are prominent pathogeneic features of Alzheimer’s Disease (AD). In recent years, impairment of autophagy has also been shown to contribute to AD progression. Here, we provide evidence that oral treatment of amyloid-prone AD-like APPPS1 mice with the autophagy activator Spermidine, a small body-endogenous polyamine often used as dietary supplement, decreased neuroinflammation and reduced neuroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Although the exact mechanisms were not elucidated, the authors speculated that autophagy [350,351] may play a role in the preservation of memory capacity in ageing. This is further reinforced by recent studies on mice which showed that supplementation by spermidine and spermine may delay brain ageing and alleviate AD pathology via mechanisms involving autophagy, promotion of ATP, reduction of ROS [353,354] and inflammation [355]. Maglione and colleagues showed that spermidine offered protection from synaptic alterations in the hippocampus of ageing mice extending their lifespan with a late treatment (starting at 18 months) [356].…”
Section: Polyaminesmentioning
confidence: 94%
“…Although the exact mechanisms were not elucidated, the authors speculated that autophagy [350,351] may play a role in the preservation of memory capacity in ageing. This is further reinforced by recent studies on mice which showed that supplementation by spermidine and spermine may delay brain ageing and alleviate AD pathology via mechanisms involving autophagy, promotion of ATP, reduction of ROS [353,354] and inflammation [355]. Maglione and colleagues showed that spermidine offered protection from synaptic alterations in the hippocampus of ageing mice extending their lifespan with a late treatment (starting at 18 months) [356].…”
Section: Polyaminesmentioning
confidence: 94%
“…In a preprint from Charité – Universitätsmedizin Berlin, dietary spermidine supplementation induced autophagy in microglia and astrocytes of APP/PS1 mouse model by decreasing the inflammasome and nuclear factor (NF)- κ B pathway activities (Ref. 234). In contrast, a tau-induced mouse model (rTg4510) exhibited an accumulation of acetylated spermidine levels, and knock-out of spermidine/spermine-N1-acetyltransferase had beneficial effects on rota-rod task, marble burying task and elevated plus-maze (Ref.…”
Section: Effects Of Lifespan-extending Interventions On Cognitive Hea...mentioning
confidence: 99%
“…Polyamines have anti-inflammatory and anti-apoptotic effects, e.g., spermidine supplementation was shown to reduce accumulation of neurotoxic soluble Aβ in early as well as late stages of Alzheimer’s disease [ 396 , 424 , 425 ]. In thioacetamide (TAA)-induced acute liver injury, spermine exerted its anti-inflammatory action by inhibiting M1 polarization, while promoting M2 polarization of Kupffer cells (KCs), decreasing their STAT1 activation, reducing the levels of IL1-β, and iNOS, and increasing STAT6 activation.…”
Section: Introductionmentioning
confidence: 99%